Development of Educational Games PERANGKA to Improve the Numeracy Skills of Children Aged 5-6 Years - Arifina, Liza Dian; Simatupang, Nurhenti Dorlina; Malaikosa, Yes Matheos Lasarus; Adhe, Kartika Rinakit (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Low numeracy skills in early childhood remain a significant issue in children's education. One contributing factor is the lack of innovative and engaging learning media aligned with children's cognitive development stages. To address this problem, this research developed an educational game called PERANGKA (Number Train Game) as a learning medium to improve numeracy skills in early childhood. This study used a Research and Development (R&D) approach with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The game was developed based on Piaget's cognitive development theory, which emphasizes the importance of using concrete and visual media in children's learning. Additionally, Mayer's multimedia theory was applied in designing the game elements. The research subjects were Group B children aged 5–6 years at Kindergarten Labschool Unesa 1 Surabaya. Data collection techniques included observation, expert validation questionnaires, and practicality assessments. The results showed that material experts gave a score of 93%, media experts 94%, and the practicality score from teachers was 90%. These findings indicate that the PERANGKA educational game is a feasible, effective, and engaging alternative learning medium for enhancing numeracy skills in early childhood.